A patient-centered ambulatory care pharmacy design to abate the real-world patient counseling challenges - Shabeer Ali Thorakkattil; Sainul Abideen Parakkal; Savera Arain; Zakariya AlDobayan (Elsevier, 2023)
Patient counseling is an important tool to help both healthcare providers and patients in achieving the desired health outcomes. It is one of the significant and well-established roles for pharmacists in the health care system, enabling them to develop a pharmacist-patient collaborative relationship to ensure medication compliance, improved adherence to the prescribed medication regimen and prevention of adverse drug events. Delivering effective and efficient patient counseling is often hindered by numerous personal and system-related challenges. Therefore, efforts to overcome these challenges necessitate developing and incorporating various tools and methods to establish an integrated patient-centered pharmacy design. This article demonstrates the development of one such integrated model in the Johns Hopkins Aramco Healthcare ambulatory care pharmacy setting. It includes components such as electronic health records, patient portal communication systems, telehealth models (both telephonic and virtual), physical redesign of the pharmacy layout, enhanced pharmacy website, and utilizing robotic dispensing systems to deliver more efficient and interactive patient counseling. The goal of implementing the innovative patient-centered pharmacy design and integration of the telehealth model was to mitigate many of the barriers faced by the pharmacist in the traditional system during patient counseling. This new integrated model provides an example for other healthcare organizations to improve patient counseling effectiveness and provide excellent patient-centered care.